Functional neurorehabilitation through the life span - Bertoti, Dolores (Philadelphia, PA : F.A. Davis Co., 2004)
Designed for physical therapist assistant students and anyone working in the rehabilitation of patients with neurologic damage, this easy-to-use textbook focuses on the framework for neurorehabilitative patient treatment. Placing an emphasis on the scientific and clinical practice, it offers problem-solving instruction on how andwhere to begin, and how to ensure that the interventions will be meaningful to individuals with neurologic damage. It examines the evolving knowledge of basic sciences, neurology, and neurophysiology, and translates these into treatment ideas for patients throughout the life span. Thetext presents "best practice" insights, made clinically meaningful and easily applicable to patient care. (Product Description)
Includes bibliographical references and index
1 13
Keywords: Nervous System Diseases -- rehabilitation; Nervous system -- Diseases -- Patients -- Rehabilitation; Occupational therapy; Occupational Therapy -- methods; Physical therapy